Les territoires français de l’automobile à l’épreuve des mutations des systèmes productifs - Dalila Messaoudi (Bulletin de l’Association de Géographes Français)
The economic and financial crisis in 2007-2008 revealed the importance of the deindustrialization era that France has entered. The economic situation and the rise of emerging countries tend to speed up this process for most of the historically industrialized countries in general and for France in particular. This speeding process seems to deteriorate the employment quality especially at a regional level. The situation rises many questions about the future of the existing production. The fall of the French car industry is highly emblematic and therefore it should lead the way to a specific analysis. For many years now, it has faced the development of emerging but also European countries. This competition has a very bad effect on national production and may lead to a decrease and eventually to the death of it.